Meningkatkan Green Performance melalui Green HRM, Budaya Organisasi, dan Green Value Strategy: Peran Mediasi Corporate Social Responsibility - Yuswardi; Muhammad Donal Mon; David Ezra Putra (Program Magister Manajemen STIE Widya Wiwaha Yogyakarta, 2026)
This study aims to examine the influence of Green Human Resource Management, Green Value Strategy, and Organizational Culture on Corporate Social Responsibility and their impact on Green Performance within hospital settings. Increasing environmental demands in the healthcare sector require hospitals to integrate environmentally responsible practices across their operational activities. The findings reveal that Green Human Resource Management, Green Value Strategy, and Organizational Culture positively affect Corporate Social Responsibility. In addition, Green Human Resource Management and Organizational Culture directly enhance Green Performance. Corporate Social Responsibility also strengthens the hospital’s environmental performance and acts as a connecting element between internal sustainability practices and environmental outcomes. These results indicate that improved environmental performance in hospitals is shaped by the combination of sustainability-oriented human resource policies, green value strategies, supportive organizational culture, and consistently implemented social responsibility initiatives.